Limiting sets of subharmonic functions and associated measures in a cone - Rashkovsky , A. Yu.; Ronkin , L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
A study is conducted of the relationship between the asymptotic behavior of a subharmonic function of finite order in a cone and the distribution of the measure associated with it.